2005
DOI: 10.1088/1742-6596/5/1/018
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios for multiplicity distributions inppcollisions in the TeV energy region

Abstract: Possible scenarios based on available experimental data and phenomenological knowledge of the GeV energy region are extended to the TeV energy region in the framework of the weighted superposition mechanism of soft and semi-hard events. KNO scaling violations, forward-backward multiplicity correlations, Hq vs. q oscillations and shoulder structures are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…We concluded that the high mu ltip licity regions in the N ch -distribution correspond to the mult i-jet events. The results were in good agreement with those discussed by Ugoccioni and Giovannini [7]. Fig.…”
Section: Trans Verse Momentum Distributionssupporting
confidence: 92%
See 1 more Smart Citation
“…We concluded that the high mu ltip licity regions in the N ch -distribution correspond to the mult i-jet events. The results were in good agreement with those discussed by Ugoccioni and Giovannini [7]. Fig.…”
Section: Trans Verse Momentum Distributionssupporting
confidence: 92%
“…We chose this selection of the polar angle reg ions from analyses of the angular distributions of the secondary charged particles. The results of distributions of N ch for zero and multi-jet events were found to be inconsistent with the experimental mu ltip licity distributions (MDs) of charged particles interpreted by fitting with the Pascal (Negative Binomial) Distributions [7].…”
Section: Introductionmentioning
confidence: 74%
“…In anticipation for the upcoming operation of LHC in 2008, multiparticle production has again become one of major discussion in high energy physics recently [1,2]. In the previous studies, negative binomial distribution (NBD), which Giovannini has shown as a solution to the stochastic branching equation [3] that governs the dynamics of multiparticle production, is usually used to describe the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed discussion of multiplicity distributions at TeV energies is given in refs. [9], and references therein.…”
Section: Introductionmentioning
confidence: 99%